Epidermal barrier and oxidative stress parameters improve during in 311 nm narrow band UVB phototherapy of plaque type psoriasis. Issue 1 (July 2018) - Darlenski, Razvigor; Hristakieva, Evgeniya; Aydin, Ufuk; Gancheva, Desisslava; Gancheva, Tanya; Zheleva, Antoaneta; Gadjeva, Veselina; Fluhr, Joachim W.
Abstract: Background: Psoriasis is a multi-systemic inflammatory disease that results from dysregulation between epidermal keratinocyte homeostasis and both innate and acquired immunity. Epidermal barrier defect has been described in psoriatic lesions. Furthermore an imbalance between pro-oxidative stress and antioxidant defense mechanisms are known in psoriasis patients. Aim: The aim of this study was to address the link between disease activity, epidermal barrier and systemic oxidative stress in the course of 311 nm narrow band ultraviolet B (NB-UVB) therapy of psoriasis. The dynamic of systemic oxidative stress parameters as well as local transepidermal water loss (TEWL) and stratum corneum hydration (SCH) was characterized before and after 311 nm NB-UVB therapy on the plaques of psoriasis vulgaris in comparison to untreated non-affected volar forearm sites of the same patients. Material and methods: 22 patients with plaque type psoriasis vulgaris and 25 gender- and age-matched healthy controls were enrolled. We assessed the psoriasis area and severity index (PASI) and the dermatology life quality index (DLQI) for monitoring disease activity, severity and self-perceived DLQI impact as patient related outcome parameter. We measured non-invasively TEWL (Tewameter TM 300) and SCH (Corneometer CM 825) and the end product of lipid peroxidation – malondialdehyde (MDA), Reactive oxygen species (ROS), ascorbyl radicals (Asc) and detoxifying activity of catalase (CAT) were measured in the peripheral blood with spectrophotometric and EPR spectroscopy methods. Results: Disease activity improved in all patients compared to baseline witnessed by significant decrease in PASI; (from 14.1 to 10.4; p < 0.0001) and DLQI (from 11.7 to 8.1; p < 0.0001). At baseline TEWL-values were significantly (p < 0.0001) higher on psoriatic plaques (16.8 g/h/m 2 ) in comparison to uninvolved skin (5.3 g/h/m 2 ); with a decrease at both sites after NB-UVB phototherapy. SCH was significantly lower at psoriatic plaque s (4.7AU) compared to uninvolved sskin (42.4AU) and increased after treatment (8.6AU) (p < 0.0001). Interestingly, SCH decrease slightly during therapy at uninvolved skin (40.6AU). ROS and Asc declined during therapy in parallel to a decrease in MDA. A mild decrease in the antioxidative enzyme CAT activity which did not reach the significance was observed. Conclusion: The presented data is shows that a clinical improvement of psoriatic plaques under NB-UVB therapy, shown in with a decreased PASI and reflected by an increase in quality of life has beneficial effects on epidermal barrier function, SCH and improvement of systemic oxidative stress parameters (ROS, MDA and Asc). We assume that the general improvement in the oxidative stress parameters along with epidermal barrier parameters reflects mainly the improvement of disease activity which overwrites the possible negative pro-oxidative effects of the UV treatment.